FEAR OF ENGLISH PUBLIC SPEAKING: CAUSES AND CONQUEST - Muhammad - Sabri (INOVISH JOURNAL, 2019)
Abstract: This study tries to find out what factors causing students’ fear of English public speaking and what methods could help them to conquer it effectively. This is a descriptive qualitative study where the data for the research were collected through a self-administered questionnaire distributed to all students of the sixth semester at English Study Program of State Polytechnic of Bengkalis – Riau. The questionnaire was set based on relevant literature review and also focused on condition of the students based on daily observation done by the researcher during his several years of teaching Public Speaking subject to the students. After collecting the data, the researcher sorted the data by summarizing and choosing the specific category, displaying and verifying the data analysis and making the conclusion from the finding data. The result of this study reveals the factors that caused the fear of English public speaking facing by the students and the methods that could help the students most effectively to conquer their fear of English public speaking.